1990
DOI: 10.1002/1097-0142(19900501)65:9<1923::aid-cncr2820650909>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of number of positive nodes in cervical carcinoma stages IB, IIA, and IIB

Abstract: Radical hysterectomy and bilateral pelvic lymphadenectomy were done on 875 patients diagnosed with cervical carcinoma Stages IB (484 patients), IIA (96 patients), and IIB (295 patients). The number of positive nodes was 0 in 620 patients (N0), one in 98 patients (N1), two to three in 80 patients (N2), four to 18 in 45 patients (N4), and unresectable in 32 patients. Cumulative 5-year survival rates were 89%, 81%, 63%, 41%, and 23%, respectively. Significant survival reduction rates (P less than 0.05) from N0 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
4
9

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 10 publications
8
107
4
9
Order By: Relevance
“…Regarding LN involvement, there is a positive association between the number of positive LNs and patient prognosis (13,14). The 5-year OS rates for patients with 0, 1 and ≥2 positive pelvic nodes were reported to be 89, 83 and 58%, respectively (P=0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding LN involvement, there is a positive association between the number of positive LNs and patient prognosis (13,14). The 5-year OS rates for patients with 0, 1 and ≥2 positive pelvic nodes were reported to be 89, 83 and 58%, respectively (P=0.007).…”
Section: Discussionmentioning
confidence: 99%
“…In cases where there is only 1 positive node, no adverse effect on patient survival has been observed, according to certain authors (16,17). Inoue and Morita (14) reported on the effect of the number of positive LNs on stage IB-IIB cervical cancer. The 5-year OS rates for patients with 0, 1, 2-3 and ≥4 positive nodes were 89, 81, 41 and 23%, respectively.…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…This noninvasive approach leads to misclassification (mostly understaging) in a considerable number of cases (10-25%), possibly resulting in suboptimal care [2][3][4], Patients with positive lymph nodes and/or clear lymph or blood vessel invasion comprise most of the misclassified cases. Most of these patients need adju vant radiation treatment leading to a higher incidence of severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, tumor spread be yond the small pelvis or lymph and blood vessel invasion cannot be detected with this type of staging. When clinical staging was compared with surgical staging, inaccuracies (mostly understaging) were found in 10-25% of patients with clinical stage IB or IIA [2][3][4]. Several authors have demonstrated reduced survival in patients with lymph node metastases and lymph or blood vessel invasion [5,6], It seems useful to develop new strategies to define subgroups of patients in order to further individualize treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis depends on pathological stage, tumor grade and histology, and the extent of lymph node (LN) metastasis [2][3][4][5][6][7] . The latter is an important prognostic factor, and the survival rates of patients with nodal metastases are significantly lower than those of patients without such metastases [2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%